2020
DOI: 10.1002/aenm.202001589
|View full text |Cite
|
Sign up to set email alerts
|

Precise Control of Phase Separation Enables 12% Efficiency in All Small Molecule Solar Cells

Abstract: Compared to conjugated polymers, small‐molecule organic semiconductors present negligible batch‐to‐batch variations, but presently provide comparatively low power conversion efficiencies (PCEs) in small‐molecular organic solar cells (SM‐OSCs), mainly due to suboptimal nanomorphology. Achieving precise control of the nanomorphology remains challenging. Here, two new small‐molecular donors H13 and H14, created by fluorine and chlorine substitution of the original donor molecule H11, are presented that exhibit a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 46 publications
0
42
0
Order By: Relevance
“…[ 14–17 ] Small‐molecule donors with their advantages of a well‐defined molecular weight and easy purification suffer less from batch‐to‐batch variations and provide a possible solution to overcome this issue. [ 12,14–25 ] Recent progress in designing small‐molecule donors, combined with control over phase separation and morphology, has pushed the PCEs of small‐molecule organic solar cells (SM‐OSCs) in which both donor and acceptor are well‐defined small molecules to above of 15%, closing in on the existing efficiency gap with the best PSCs. [ 12,20,26 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 14–17 ] Small‐molecule donors with their advantages of a well‐defined molecular weight and easy purification suffer less from batch‐to‐batch variations and provide a possible solution to overcome this issue. [ 12,14–25 ] Recent progress in designing small‐molecule donors, combined with control over phase separation and morphology, has pushed the PCEs of small‐molecule organic solar cells (SM‐OSCs) in which both donor and acceptor are well‐defined small molecules to above of 15%, closing in on the existing efficiency gap with the best PSCs. [ 12,20,26 ]…”
Section: Introductionmentioning
confidence: 99%
“…
of purity and molecular weight distribution are almost inevitable and limit the reproducibility of PSCs, hindering progress toward technology development and commercialization. [14][15][16][17] Small-molecule donors with their advantages of a welldefined molecular weight and easy purification suffer less from batch-to-batch variations and provide a possible solution to overcome this issue. [12,[14][15][16][17][18][19][20][21][22][23][24][25] Recent progress in designing small-molecule donors, combined with control over phase separation and morphology, has pushed the PCEs of small-molecule organic solar cells (SM-OSCs) in which both donor and acceptor are well-defined small molecules to above of 15%, closing in on the existing efficiency gap with the best PSCs.
…”
mentioning
confidence: 99%
“…These unsatisfactory results mainly originate from the limited materials system and the hardly controlled morphology. While thanks to the innovation of NFAs as well as SMDs, we have witnessed impressive results with PCEs around 9% to 12% since 2017 35‐40 . Recently, Hou et al demonstrated an encouraging PCE of 15.3% (certified 15.1%) 41 for the binary devices.…”
Section: Introductionmentioning
confidence: 89%
“…The most widely utilized solution-based spin coating method to prepare thin OSCs active layers is essentially a crystallization process of multiple molecules. In this process, the phase separation occurs and largely determines whether or not the resulting film will form a nanoscale interpenetrating network structure, which in turn affects the performance of the final device (Bin et al, 2020). The crystallinity of the donor and acceptor molecules can be regarded as an important driving force for obtaining suitable phase separation for both polymers and small molecules and therefore determines the film's morphology and affects the final device performance (Heeger, 2014).…”
Section: The Relationship Between Crystallinity and Film Morphology Omentioning
confidence: 99%
“…Under the circumstance, the domain size of the active layer film should be equivalent to the exciton diffusion length of the involved materials while maintaining beneficial contact with the adjacent layers. Such a morphology, coupled with good phase purity, would enable the process of photoexcitation, exciton diffusion, charge separation, and charge transport in the device to be highly efficient, ultimately resulting in excellent device photoelectric performances (Bin et al, 2020). Therefore, attaining precise control of the crystallinity of materials and the crystallization process during device fabrication is important for obtaining high-performance devices.…”
Section: The Relationship Between Crystallinity and Film Morphology Omentioning
confidence: 99%